Meningkatkan Kemampuan Membaca Permulaan Menggunakan Metode Fernald Bagi Disabilitas Intelektual Ringan - Sinaga, Rindu; Iswari, Mega; Damri, Damri; Safaruddin, Safaruddin; Zulpiani, Mardhatillah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aimed to improve early reading skills through the implementation of the Fernald method among third-grade students with mild intellectual disabilities at SLB Negeri Pematang Siantar. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects consisted of two students with mild intellectual disabilities, identified as IA and AM. Based on the initial assessment results, the students’ early reading abilities were classified as low, with achievement percentages of 30% for IA and 25% for AM. The implementation of Cycle I showed an improvement in early reading skills for both students, with IA and AM each achieving 45%. Furthermore, a more significant improvement was observed in Cycle II, where IA achieved 80% and AM achieved 75%. Data were collected through observations using an early reading skills assessment checklist, while data analysis was carried out using descriptive quantitative techniques by comparing students’ achievement levels across cycles. The findings indicate that the application of the Fernald method was effective in improving early reading skills among students with mild intellectual disabilities. These results suggest that reading instruction employing a multisensory approach—integrating visual, auditory, kinesthetic, and tactile modalities—can enhance students’ motivation, comprehension, and early reading outcomes in accordance with the characteristics of learners with mild intellectual disabilities.